Abundance, parity, and Japanese encephalitis virus infection of mosquitoes (Diptera: Culicidae) in Sepang District, Malaysia - Vythilingam, I.; Oda, K.; Mahadevan, S.; Abdullah, G.; Thim, C.S.; Hong, C.C.; Vijayamalar, B.; Sinniah, M.; Igarashi, A. (1997)
A 2-yr study of Japanese encephalitis (JE) virus in Sepang District, Selangor, Malaysia, was carried out to identify the mosquito vectors and to determine their seasonal abundance, parity, and infection rates. In total, 81,889 mosquitoes belonging to 9 genera and > 50 species were identified from CDC trap collections augmented with dry ice during 1992 and 1993. Culex tritaeniorhynchus Giles and Culex gelidus Giles were the most abundant species, and both increased in numbers with increases in rainfall. Overall, 45 JE virus isolations were made from 7 species-Cx. tritaeniorhynchus (24), Cx. gelidus (12), Culex fuscocephala Theobald (2), Aedes butleri Theobald (4), Culex quinquefasciatus Say (1), Aedes lineatopennis Ludlow (1), and Aedes (Cancraedes) sp. (1). Based on elevated abundance and JE infection rates, Cx. tritaeniorhynchus appears to be the most important vector of JE virus in Sepang